Health-related quality of life and patient-reported outcomes of ofatumumab plus fludarabine and cyclophosphamide versus fludarabine and cyclophosphamide in the COMPLEMENT 2 trial of patients with relapsed CLL. Issue 7 (3rd July 2017) - Robak, Tadeusz; Warzocha, Krzysztof; Govind Babu, K.; Kulyaba, Yaroslav; Kuliczkowski, Kazimierz; Abdulkadyrov, Kudrat; Loscertales, Javier; Kryachok, Iryna; Kłoczko, Janusz; Rekhtman, Grygoriy; Homenda, Wojciech; Błoński, Jerzy Z.; et al.
Abstract: Chronic lymphocytic leukemia (CLL) is an incurable disease. Quality of life during treatment and periods of subsequent remission is therefore vital. Health-related quality of life (HRQoL) was compared in relapsed CLL during and after treatment with ofatumumab combined with fludarabine and cyclophosphamide versus fludarabine and cyclophosphamide alone. The European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 v3 and QLQ-CLL16 were used to assess HRQoL in this open-label, phase 3 study. Improvements in prespecified domains of patient-reported outcomes (Global Health Status [GHS]/HRQoL and B symptom scores) were recorded in both treatment arms after three cycles and were sustained after 18 months of follow-up. The two treatment arms were not significantly different at the nominal 0.05 level for GHS/HRQoL ( p = .7278) or B symptoms ( p = .5968). Small improvements in quality of life were maintained after therapy. The addition of ofatumumab was without any adverse impact on HRQoL (NCT00824265).